2008
DOI: 10.1007/s11095-008-9749-2
|View full text |Cite
|
Sign up to set email alerts
|

Meal-Induced Acceleration of Tablet Transit Through the Human Small Intestine

Abstract: The timing of food ingestion has a clear effect on small intestinal transit of single-unit formulations and this has implications for drug bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 32 publications
7
43
1
Order By: Relevance
“…With these types of dosage forms, dissolution media and pH selection will be critical when developing an IVIVR/ IVIVC and these factors need to be considered early in the predictive dissolution testing design stage. [87][88][89] A comparison of the amount of dissolution media used in these studies is given in Figure 2a. Fiftytwo percent of the studies used 900 mL and 32% used 500 mL; these are typical volumes for many dissolution studies.…”
Section: In Vitro Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…With these types of dosage forms, dissolution media and pH selection will be critical when developing an IVIVR/ IVIVC and these factors need to be considered early in the predictive dissolution testing design stage. [87][88][89] A comparison of the amount of dissolution media used in these studies is given in Figure 2a. Fiftytwo percent of the studies used 900 mL and 32% used 500 mL; these are typical volumes for many dissolution studies.…”
Section: In Vitro Factorsmentioning
confidence: 99%
“…In contrast to the majority of the dissolution medium volumes (500-900 mL) used in the papers being reviewed, Table 4 reveals that the fasted GI tract fluid volumes are approximately 100 mL or lower. 98,87 The mean regional fluid volumes in the stomach and along the small and large intestines under the fasted state have been determined to be approximately 45, 105, and 13 mL, respectively. In the fed state, the mean regional free fluid volumes in the stomach (meal and fluid combined), the small and large intestines were observed to be approximately 686, 54, and 11 mL, respectively, which are significantly different than the fasted state.…”
Section: In Vivo Factorsmentioning
confidence: 99%
“…Correspondingly, 52 subject groups were included within the analysis. The analysis included 11 investigations (Davis et al, 1984a(Davis et al, ,b, 1986a(Davis et al, , 1987Khosla et al, 1989;Madsen and Jensen, 1989;Coupe et al, 1991;Madsen, 1992;Billa et al, 2000;Bouras et al, 2004;Fadda et al, 2009), where estimates of intestinal transit were pooled between test conditions (e.g., fasted versus fed). For each of these investigations, mean intestinal transit times were not found to be significantly different between treatment arms as either denoted by the authors' results or independently confirmed using a paired Student's t test (P .…”
Section: Resultsmentioning
confidence: 99%
“…8, 9a, 9b, 12a, and 12b for three drug constructs in a patient described by average physiological parameters. The value for small intestinal fluid volume (V l ) is 70 mL and the transit time (T l r) is 180 min, which represent median values from the literature (22,37,(44)(45)(46). The plateau concentration (C g p) was set to 10 μg/mL to reflect the low solubility values for many BCS II compounds, particularly those for which dissolution enhancement strategies, such as amorphization, are sought.…”
Section: Methodsmentioning
confidence: 99%